Synchronous presentation of gastrointestinal stromal tumor of stomach and neuroendocrine tumor of Jejunum as acute intestinal obstruction - Manjula K; Kalyani R; Shilpa MD; Mohan Kumar K (Journal of Clinical and Biomedical Sciences)
Neuroendocrine tumors (NETs) arise from the diffuse components of the endocrine system A patient with jejunoileal NETs usually presents with vague abdominal complains which may progress to intestinal ob-struction. Gastrointestinal stromal tumors (GIST) are mesenchymal tumors arising from interstitial cell of Cajal or pacemaker cells. GIST is the most common mesenchymal tumor of the abdomen. We are here by reporting a rare synchronous tumor for awareness and better management of patents. Keywords: Synchronous, Gastrointestinal tumors, stomach, Jejunum, NETs.